Characterizing barriers to antibiotic stewardship for skin and soft-tissue infections in the emergency department using a systems engineering framework - Michael S. Pulia; Rebecca J. Schwei; Steven P. Hesse; Nicole E. Werner (Cambridge University Press, 2022)
Abstract Objective: Skin and soft-tissue infections (SSTIs) account for 3% of all emergency department (ED) encounters and are frequently associated with inappropriate antibiotic prescribing. We characterized barriers and facilitators to optimal antibiotic use for SSTIs in the ED using a systems engineering framework and matched them with targeted stewardship interventions. Design and participants: We conducted semistructured interviews with a purposefully selected sample of emergency physicians. Methods: An interview guide was developed using the Systems Engineering Initiative for Patient Safety (SEIPS) framework. Interviews were recorded, transcribed, and analyzed iteratively until conceptual saturation was achieved. Themes were identified using deductive directed content analysis guided by the SEIPS model. Results: We conducted 20 interviews with physicians of varying experience and from different practice settings. Identified barriers to optimal antibiotic prescribing for SSTIs included poor access to follow-up (organization), need for definitive diagnostic tools (tools and technology) and fear over adverse outcomes related to missed infections (person). Identified potential interventions included programs to enhance follow-up care; diagnostic aides (eg, rapid MRSA assays for purulent infections and surface thermal imaging for cellulitis); and shared decision-making tools. Conclusions: Using a systems engineering informed qualitative approach, we successfully characterized barriers and developed targeted antibiotic stewardship interventions for SSTIs managed in the ED work system. The interventions span multiple components of the ED work system and should inform future efforts to improve antibiotic stewardship for SSTIs in this challenging care setting.